Long-Term Effects of Unpaid Overtime: Evidence for West Germany - Markus Pannenberg (Institute for the Study of Labor (IZA), 2002)
Why do people work unpaid overtime? We show that remarkable long-term labor earnings gains are associated with unpaid overtime in West Germany. A descriptive analysis suggests that over a 10-year period workers with unpaid overtime experience on average at least a 10 percentage points higher increase in real labor earnings than their co-workers. Applying panel data models this result generally holds. Furthermore, we find some evidence for gender specific differences with respect to the effects of unpaid overtime work. Our results point to the importance of investment in current working hours beyond the standard work week to enhance real earnings prospects.
Keywords: J33; J31; J23; J22; 330; overtime; overtime compensation; labour earnings; linear panel data models; Überstunden; Einkommen; Bildungsertrag; Erwerbsverlauf; Schätzung; Geschlecht; Deutschland